(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
A local area network (LAN) is currently being used by many people in research, school assignment, etc. A LAN typically spans a single building, campuses, and other small areas. Generally,a LAN is considered a small network that exists in a single location. Most LANs connect workstations or personal computers. Hence, many users connect to a LAN and can easily share a file. During the planning stage, the group prepared the questionnaire needed for our client to gather information about the problem encountered without the use of LAN. Our group analyzed the gathered information about having a LAN connection to their hall. It is also faster to transferring or sharing files, thereby decreasing the time consumed. It helps the staff in the barangay hall to lessen the work they do. We also told the client about the possible risk they may encounter during this session. A LAN is extremely common and is designed to stand up. We set up a LAN for the admin and staff of the barangay hall of Brgy. Bagbag, Sauyo, Quezon City. A high-speed transmission capability was used as the basis for a general-purpose data transfer network. There are two basic issues in the LAN design. First, how should the hardware realize the network be organized to provide reliable high-speed communication at minimum cost? With the low cost of the raw transmission capability, care is required to keep the associated hardware costs correspondingly low. Second, what protocols should be used for the operation of the network? After we set up the LAN, we immediately run a test to know the possible outcome of the LAN we set. If there is any problem, then we can fix it. Lastly, we gave them a warranty; they can contact us if the system will pose a problem and we will fix it right away. We also gave a guide in purchasing connection devices with a high specification to lessen the time consumed by the staff. LAN is becoming successful because it is now more affordable and is available like other devices. We also discussed with the client the devices we needed and what was the functions of these devices to the LAN we created.